1999
DOI: 10.1093/jjco/29.6.294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Magnetic Resonance Cholangiopancreatography for the Diagnosis of Cystic Tumor of the Pancreas Compared with Endoscopic Retrograde Cholangiopancreatography and Computed Tomography

Abstract: Background: Cystic tumor of the pancreas has been investigated by a variety of imaging techniques. Magnetic resonance cholangiopancreatography (MRCP) is being widely used as a non-invasive diagnostic modality for investigation of the biliary tree and pancreatic duct system. The purpose of this study was to compare MRCP images with those of endoscopic retrograde cholangiopancreatography (ERCP) and computed tomography (CT) in order to clarify the diagnostic efficacy of MRCP for cystic tumor of the pancreas. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Sahani et al [25] have reported that CT and MRI are reasonably and similarly accurate in both detection and characterization of cystic pancreatic lesions. Furthermore, Mera et al [26] have reported that CT is superior to MRCP for the detection of the internal features of cystic tumor of the pancreas: detection rate of the septum and solid components inside the cystic tumor of the pancreas were 100 and 90% for CT, and 58.3 and 20.0% for MRCP, respectively. They discussed that one of the limiting factors for the MRCP image is a maximum intensity projection algorithm to create three-dimensional images of the pancreatic duct system.…”
Section: Discussionmentioning
confidence: 99%
“…Sahani et al [25] have reported that CT and MRI are reasonably and similarly accurate in both detection and characterization of cystic pancreatic lesions. Furthermore, Mera et al [26] have reported that CT is superior to MRCP for the detection of the internal features of cystic tumor of the pancreas: detection rate of the septum and solid components inside the cystic tumor of the pancreas were 100 and 90% for CT, and 58.3 and 20.0% for MRCP, respectively. They discussed that one of the limiting factors for the MRCP image is a maximum intensity projection algorithm to create three-dimensional images of the pancreatic duct system.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, however, mucinous cystic neoplasms may show this characteristic; and, of course, intraductal papillary mucinous tumors (IPMTs) by definition show ectatic changes in the pancreatic duct which may include cystic dilatation of the branch ducts [3,7,8]. Magnetic resonance cholangiopancreatography (MRCP) is a relatively new technique that has shown promise in better defining the relationship between cystic lesions and the pancreatic duct, but until there is further refinement, its clinical use should probably be corroborated with other imaging studies such as CT [9]. Endoscopic ultrasound is emerging as another powerful tool in the differential diagnosis of pancreatic cystic lesions.…”
Section: Pseudocystsmentioning
confidence: 99%
“…In most cases, T2WI show typical lobular and marked hyperintense mass lesions. On MRCP, SCT is marked by strong hyperintensity, reflecting its cystic nature [21]. Thus, diagnosis of most cases is not difficult.…”
Section: Serous Cystic Tumormentioning
confidence: 99%